Power Influence Towards Society Protest Behavior Around The Extractive Petroleum Industry - Nadya Izana, Nyimas; K. Pandjaitan, Nurmala (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2015)
One of the extractive petroleum industries that are currently present in Indonesia is the PCI Industry which cooperates with Pertamina. PCI Industry is located in Bojonegoro, East Java and established in 2002. Ever since the presence of the extractive petroleum industry, conflict with society is started to begin. The method used in this study was a quantitative method that was supported by quantitative data. Qualitative data were obtained by observations and in-depth interviews. Quantitatif data using questionnaires were obtained from two villages with 100 respondents. Respondents were divided into two geoups: responden who did non participate in the protest and respondents who participated in the protest.This study aims to analyze the root problem of public protest occurence towards the PCI Industry, analyze the presence of PCI Industry that raises a certain protest behavior of society and analyze the effect of local leaders power on the dynamics and behavior of the society protest. The result showed that the root problem of public protes occurence towards the PCI Industry is an opportunities to work in the PCI Industry, CSR funds, environmental demanding. The protest behavior of local people due to the presence of the PCI Industry is in accordance with the theory of planned behavior which mentions that attitude is not enough to determine behavior, but there are subjective norms and perceived behavioral control. The effect of local leader power on the dynamics and behavior of the society protest is appreciable. Keywords: attitudes, behavior control, power, subjective norms, work and business opportunities